Effects of dietary Pb on antioxidant defense systems and microstructure of hepatopancreas in tilapia (Oreochromis niloticus) - DAI Wei; JIN Cheng-guan; FU Ling-lin; DU Hua-hua; XU Zi-rong (浙江大学学报. 农业与生命科学版)
Tilapia were exposed to dietary Pb at concentrations of 0,100,400 and 800 μg·g-1 dry weight for 60 days, and effects of dietary Pb on microstructure, malonyldialdehyde (MDA) content and antioxidant ability of hepatopancreas were investigated. The results show that MDA content in hepatopancreas increased and total antioxidant capacity (T-AOC) and glutathione (GSH) levels decreased with the increases of dietary Pb concentrations. Glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activities were induced by dietary Pb. Pb concentration-related lesions could be detected in histological sections of hepatopancreas. The results above suggest that oxidative damage may be one of the reasons for dietary Pb toxicity on hepatopancreas of tilapia.